Suhuang Antitussive Capsule Ameliorates Corticosteroid Insensitivity in Cough Variant Asthma Guinea Pigs by Inhibiting p38 MAPK Signal Pathway. (17th March 2022) - Lyu, Tianyi; Li, Demin; Zhang, Haojun; Chen, Siyi; Yang, Daowen
Abstract : Purpose/Objective. Inhaled corticosteroids (ICS) are the most effective treatment for asthma. However, some asthmatic patients do not respond to ICS treatment due to insensitivity. Thus, some studies have attempted to identify combination treatments to resolve this clinical problem. Cough variant asthma (CVA) is well established as a specific asthma phenotype. In this study, we examined whether the traditional medicine Suhuang (a combination of several traditional Chinese medicinal plants) could enhance the effect of Budesonide (BUD) by ameliorating corticosteroid insensitivity via p38 MAPK signal pathway in CVA guinea pig. Methods . The CVA guinea pig model was successfully established by use of ovalbumin (OVA) sensitization and cigarette smoke (CS) exposure. The guinea pigs were divided into 6 groups: a control group, an OVA model group, an OVA + CS model group, a Suhuang treatment group, a BUD treatment group, and a combination ( Suhuang and BUD) treatment group. The effects of the treatment were determined by measuring lung function (RI/Cydn) and cough symptoms (coughs number/cough latency) as outcome criteria. The levels of inflammatory cytokines in bronchoalveolar lavage fluid (BALF) were determined by ELISA. Lung tissues were stained by hematoxylin and eosin (H&E). The expressions of GR/total p38 MAPK/p-p38 MAPK were detected by Western blot. The MKP-1 mRNA levels were detected by RT-PCR. Results . Combination treatment significantly decreased RI/coughs numbers and increased Cydn/cough latency. Significantly, the results indicated that combination treatment decreased injury to pulmonary tissues. Results also revealed that levels of inflammatory cytokines were reduced in all treatment groups but most markedly in the combination treatment group. Moreover, Suhuang treatment significantly ameliorated corticosteroid insensitivity by improving the expression of glucocorticoid receptors (GR). The expressions of total p38 MAPK and p-p38 MAPK in lung tissue were significantly inhibited in the Suhuang and combination treatment groups. The MKP-1 mRNA levels in Suhuang and combination treatment groups were also increased significantly. Conclusion . Suhuang was effective for reversing corticosteroid insensitivity by regulating the p38 MAPK signal pathway, and combining BUD and Suhuang treatment showed synergistic interactions in CVA guinea pigs. Our findings showed that this combination therapy might be a promising therapeutic agent for CVA and also clarified its underlying mechanism of action, providing a theoretical basis for clinical combination treatment with Suhuang and BUD in CVA patients.